SAT0093 Hand Joint Inflammation on Fluorescence Optical Imaging Reveal Distinct Patterns in Seropositive and Seronegative Early Rheumatoid Arthritis. (15th July 2016) - Kisten, Y.; af Klint, E.; Levitsky, A.; Rezaei, H.; Györi, N.; Karlsson, A.; van Vollenhoven, R.; Arnaud, L.
Abstract : Background: Detection of abnormal Rheumatoid Arthritis (RA) related autoantibodies, Rheumatoid Factor (RF) and Anti-Citrullinated Peptide Antibody (ACPA), along with Musculoskeletal ultrasound (MSUS) play a critical role in the diagnosis of early RA (eRA). Fluorescence optical imaging (FOI) is an emerging modality designed for the hands and wrists that detects subclinical hand joint inflammation 1 and may therefore prove valuable in the assessment of eRA. Objectives: Here, we analyzed the FOI results of eRA patients and investigate whether patterns of hand joint inflammation may distinguish seropositive from seronegative RA. Methods: In FOI, Inflammation is considered positive, when altered microcirculation (capillary leakage/perfusion) is seen as abnormally increased focal optical signal intensities by visual inspection of the entire image series in real-time (360 seconds all 34 joints: 3 wrists, 5 MCPs, 5 PIPs and 4 DIPs, bilaterally are evaluated using post-processing imaging techniques). Unsupervised ascending hierarchical clustering was used to identify clusters of patients with different patterns of joint involvement in FOI. The robustness of the clustering was verified using another clustering method (k-means), and agreement between the 2 methods was assessed using Cohen's kappa. Baseline clinical and biological characteristics of patients were compared between the clusters using non-parametric tests. Results: Out of 1326 joints of 39 eRA patients (26 females; 9 with erosive RA; 54% RF+; and 69% ACPA+), 400 (30%) were considered positively inflamed by FOI. The mean (±SD) number of active joints detected by FOI was 10.3 ± 7.2. Clustering of joint involvement according to the FOI distinguished 2 separate clusters of patients: Cluster1 (n=29) and Cluster2 (n=10). The proportion of seropositive patients was significantly higher in cluster 1 versus cluster 2 (26/29 versus 3/10, p<0.01) (figure ). The distribution of inflammation throughout the joints, except for right MCP2, PIPs 5, left MCP1 & DIPs in cluster 2 displayed distinguishable patterns (p<0.05) compared to cluster 1, which showed joint inflammation to be largely concentrated around wrists, right MCP2, bilateral MCP3, and to a lesser degree around PIPs 2–4, and left MCP2. The DIPs showed no significant differences between clusters. Conclusions: Two separate patterns of inflammatory joint involvement may be distinguished in early RA, using fluorescence optical imaging. The proportion of seropositive patients was significantly different between these patterns, suggesting that FOI identifies patterns of joint involvement that are different for seropositive and seronegative RA. References: Kisten Y, Györi N, af Klint E, et al. 2015 Detection of clinically manifest and silent synovitis in the hands and wrists by fluorescence optical imaging. RMD Open 2015;1: e000106. doi:10.1136/ rmdopen-2015-000106 (http://rmdopen.bmj.com/content/1/1/e000106.full.pdf+html ) Disclosure of Interest: None declared